The complex interaction of media and health profession: Key aspects in crisis situations - Sabljak, Danijel; Karamatić, Anđela; Lujanac, Dijana (Crisis Management Days, 2024)
This paper is researching the complex interaction between the media and the public health care providers, with special attention focused on their dynamic relationship in crisis situations. It is important to analyse the required information that the media is demanding in those situations, which are: the details about the beginning of the crisis, aspects of the problem solving process, material losses, causes of the crisis and the answers to the crisis. Special importance is given to the role of media because of their ability to spread relevant healthcare information, encouragement of the rights of the patients, and new accomplishments in the field of medicine. This paper is also reasearching the key element of cooperation between health care professionals and journalists in securing of the adequate informing of the public, which is, in example, the practice of Motovun summer school of advancing the healthcare profession. Also, this paper is analysing the key functions of the hospital command group and the strategies of communication during crisis situations, with special care focused on the importance of coordinated activity and pre-planned actions. Successful communication between media and healthcare experts is the key to effective crisis management and promoting healthcare in society. It is important for this communication to be based on respecting ethical standards and making sure that only the verified informations about the crisis situation is spread via the media, so that the integrity and accuracy of the information transmitted to the public is always present.